2016
DOI: 10.4041/kjod.2016.46.5.280
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of tooth movement in Class II malocclusions treated without extraction by orthodontic mini-implant anchorage

Abstract: ObjectiveThe aim of this study was to analyze tooth movement and arch width changes in maxillary dentition following nonextraction treatment with orthodontic mini-implant (OMI) anchorage in Class II division 1 malocclusions.MethodsSeventeen adult patients diagnosed with Angle's Class II division 1 malocclusion were treated by nonextraction with OMIs as anchorage for distalization of whole maxillary dentition. Three-dimensional virtual maxillary models were superimposed with the best-fit method at the pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…Most previous studies on orthodontic tooth movement have compared only the differences between the pretreatment and posttreatment periods. 5 6 7 8 During treatment, however, clinicians frequently have to evaluate tooth movement to decide whether to change the arch wires and/or biomechanics. However, acquiring repetitive cephalograms and CBCT images increases the risk of radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies on orthodontic tooth movement have compared only the differences between the pretreatment and posttreatment periods. 5 6 7 8 During treatment, however, clinicians frequently have to evaluate tooth movement to decide whether to change the arch wires and/or biomechanics. However, acquiring repetitive cephalograms and CBCT images increases the risk of radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“… 2 3 4 Some investigators tried to evaluate orthodontic tooth movement by superimposing digital models obtained from dental casts. 5 6 7 8 However, their evaluations compared only the differences between the pretreatment and posttreatment periods. Consequently, much important information on various tooth movements during treatment, especially during initial leveling and alignment, were overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…The reference points, lines, and planes used for measurements in the present study are shown in Figure 4. The facial axis (FA) points19 of maxillary teeth have been used as reference points for measurement in previous studies718 because incisal edges or cusp tips could be changed during orthodontic treatment. Therefore, the FA points were used as the reference points for all measurements in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Various treatment methods have been introduced to correct Class II malocclusion, depending on the severity of the discrepancy. These treatments include orthopedic treatment, premolar or molar extraction, multiloop edgewise arch wire (MEAW) technique,12 intermaxillary elastics, maxillary molar distalization combined with headgear or intraoral appliances, such as superelastic NiTi wires,3 distal jets,4 and molar sliders,5 orthodontic mini-implants (OMI),67 and surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size calculation was based on an alpha significance level of 5% and a beta of 20%, to detect a mean difference of 2.04 mm, with a standard deviation of 1.41 mm in the sagittal displacement of the maxillary first molar, reported in a previous study. 21 A minimum of 11 patients were required in each group based on the sample size calculation. Thus, to increase the power of the study 17 patients were included in each group.…”
Section: Methodsmentioning
confidence: 99%